2016
DOI: 10.1542/peds.2015-1839
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Experiences in Early Childhood and Kindergarten Outcomes

Abstract: OBJECTIVE: To examine associations between adverse childhood experiences (ACEs) in early childhood and teacher-reported academic and behavioral problems in kindergarten. METHODS:We conducted a secondary analysis of data from the Fragile Families and Child Wellbeing Study, a national urban birth cohort. Subjects with primary caregiver-reported information on ACE exposures ascertained at 5 years and teacher-reported outcomes at the end of the child's kindergarten year were included. Outcomes included teacher rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
124
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(141 citation statements)
references
References 41 publications
(36 reference statements)
4
124
0
2
Order By: Relevance
“…In a study examining ACEs among a pediatric sample, exposure to 4 or more ACEs was associated with 33 times the odds of reporting a learning or behavioral problem as compared to children without ACE exposure (Burke et al, 2011). Other studies have found substantial increases in attention and behavioral problems among children as young as 5 after cumulative ACE exposure (Jimenez et al, 2016; McKelvey et al, 2016). These studies advance the ACE literature by indicating that cumulative adversity is not only associated with strong effects on adulthood health outcomes but also childhood behavioral problems.…”
Section: Introductionmentioning
confidence: 90%
“…In a study examining ACEs among a pediatric sample, exposure to 4 or more ACEs was associated with 33 times the odds of reporting a learning or behavioral problem as compared to children without ACE exposure (Burke et al, 2011). Other studies have found substantial increases in attention and behavioral problems among children as young as 5 after cumulative ACE exposure (Jimenez et al, 2016; McKelvey et al, 2016). These studies advance the ACE literature by indicating that cumulative adversity is not only associated with strong effects on adulthood health outcomes but also childhood behavioral problems.…”
Section: Introductionmentioning
confidence: 90%
“…22 The FFCWS data has been previously used to study associations between ACEs occurring in early childhood and kindergarten outcomes. 17 The current study used data from the 5-year and 9-year follow-up interviews, which includes information on approximately 84% and 74%, respectively, of the baseline sample.…”
Section: Methodsmentioning
confidence: 99%
“…8-16 More recent work has linked ACEs to poor academic and behavioral outcomes in kindergarten and poor school engagement and behavior problems in middle childhood. 17-19 Whereas associations between ACEs and parent-reported ADHD has been reported in past work, 18-20 to our knowledge no studies have examined associations between ACEs occurring at different developmental periods in childhood and ADHD. The answer to this question can elucidate underlying pathways connecting ACEs to ADHD and inform interventions.…”
mentioning
confidence: 92%
“…Further, although not specific to children zero to two years old, children under 6 experience more ACEs than any other age (Thompson et al, 2015). Multiple ACEs in early childhood are associated with impaired social-emotional development (McKelvey, Whiteside-Mansell, Connors-Burrow, Swindle, & Fitzgerald, 2016), increased risk of polyvictimization across childhood (Grasso, Ford, Dierkhising, Branson, & Lee, 2015), belowaverage academic literacy skills and behavior problems (Jimenez, Wade, Lin, Morrow, & Reichman, 2016), and increased rates of PTSD and internalizing symptoms in adulthood (Grasso et al, 2015). Taken together, these findings suggest that children zero to two years old are at risk of increased exposure to future experiences of trauma throughout childhood, as well as other potential negative developmental outcomes.…”
Section: Impact Of Adversitymentioning
confidence: 99%